Persekongkolan Tender Paket Pekerjaan Pembangunan Rumah Sakit Daerah Provinsi Aceh (Studi Putusan KPPU Nomor 04/KPPU-L/2020) - Bimantara Fauzan Kusuma; Nanang Suparto (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2022)
In the current era, of course, hospital facilities and infrastructure need to be updated and repaired to be able to keep up with the evolving times. The hospital is a place that has a vital role in every country and even every region. Hospital obligations have also been regulated in Law Number 11 of 2020 concerning Job Creation Article 29 which requires hospitals to provide proper public facilities and infrastructure. This can be realized by renovating hospitals for the better, one of which is by carrying out the procurement of goods/services. The government has issued a legal provision, namely Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. It aims to provide signs and activities that are prohibited by business actors from conducting business activities. One example is the case of tender conspiracy. There are still some business actors who in carrying out their business activities carry out unfair business competition. This happened in the tender for the hospital construction work package in the Aceh Province. There is a conspiracy in the registration of the work package tender by the bidders which has been followed up by KPPU with the issuance of KPPU's Decision Number 04/KPPU-L/2020. The business actor referred to as the reported party in the decision has violated Article 22 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition regarding conspiracy among bidders. The parties who are reported are PT. Mina Fajar Abadi, PT Sumber Alam Sejahtera, PT Arafah Alam Sejahtera, PT Betesda Mandiri, PT Eka Jaya Lestari, PT Adhi Putra Jaya, Construction Working Group-LXXXIX Aceh Government Goods and Services Procurement Bureau for Fiscal Year 2018. This case was analyzed with three discussions, namely: The legal standing of the parties in litigation at KPPU, the suitability of the legal considerations of KPPU's Decision Number 04/KPPU-L/2020 with Law Number 5 of 1999, Legal Consequences of KPPU's Decision Number 04/KPPU-L/2020.